An easy synthetic way to exfoliate and stabilize MWCNTs in a thermoplastic pyrrole-containing matrix assisted by hydrogen bonds. Issue 89 (9th September 2016) - Araya-Hermosilla, R.; Pucci, A.; Araya-Hermosilla, E.; Pescarmona, P. P.; Raffa, P.; Polgar, L. M.; Moreno-Villoslada, I.; Flores, M.; Fortunato, G.; Broekhuis, A. A.; Picchioni, F.
Abstract : MWCNTs were dispersed in a thermoplastic polymer containing pyrrole units in the main chain and hydroxyl pendant groups, affording a well-distributed percolative network. The resulting soft nanocomposite shows stable conductive behavior. Abstract : This work focuses on the design of an engineered thermoplastic polymer containing pyrrole units in the main chain and hydroxyl pendant groups (A-PPy-OH), which help in achieving nanocomposites containing well-distributed, exfoliated and undamaged MWCNTs. The thermal annealing at 100 °C of the pristine nanocomposite promotes the redistribution of the nanotubes in terms of a percolative network, thus converting the insulating material in a conducting soft matrix (60 μΩ m). This network remains unaltered after cooling to r.t. and successive heating cycles up to 100 °C thanks to the effective stabilization of MWCNTs provided by the functional polymer matrix. Notably, the resistivity–temperature profile is very reproducible and with a negative temperature coefficient of −0.002 K −1, which suggests the potential application of the composite as a temperature sensor. Overall, the industrial scale by which A-PPy-OH can be produced offers a straightforward alternative for the scale-up production of suitable polymers to generate multifunctional nanocomposites.